2019
DOI: 10.1097/mrm.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inflammatory markers extracted from complete blood count and active pulmonary tuberculosis

Abstract: Background: Pulmonary tuberculosis (PTB) is a fatal infectious disease and remains a major global health problem especially in undeveloped countries. Delay in diagnosis and treatment may cause worsening of the disease, increasing the risk of mortality and easily spreading. This investigation aims to explore the correlation between inflammatory markers extracted from complete blood count (CBC) including red cell distribution width (RDW), neutrophil-to-lymphocyte ratio, RDW to platelet count ratio (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[36][37][38][39] Findings from earlier studies in adults have also shown the association of higher ratios in TB disease when compared to healthy controls. [15][16][17][18][20][21][22][23][40][41][42][43][44][45][46] One study from Spain including 60 adults (21 with TB disease, 19 with TB infection and 20 healthy TB exposed) reported a sensitivity of 77% and a specificity of 81% (cutoff of 2.85 and AUC of 0.83) to classify patients with TB disease versus exposed uninfected individuals. 40 Another study from Turkey including 134 adults (51 with TB disease, 40 with sarcoidosis and 43 controls) reported a sensitivity of NLR of 88% and a specificity of 80% (cutoff of 2.16 and AUC of 0.92) to classify patients with TB disease versus controls.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] Findings from earlier studies in adults have also shown the association of higher ratios in TB disease when compared to healthy controls. [15][16][17][18][20][21][22][23][40][41][42][43][44][45][46] One study from Spain including 60 adults (21 with TB disease, 19 with TB infection and 20 healthy TB exposed) reported a sensitivity of 77% and a specificity of 81% (cutoff of 2.85 and AUC of 0.83) to classify patients with TB disease versus exposed uninfected individuals. 40 Another study from Turkey including 134 adults (51 with TB disease, 40 with sarcoidosis and 43 controls) reported a sensitivity of NLR of 88% and a specificity of 80% (cutoff of 2.16 and AUC of 0.92) to classify patients with TB disease versus controls.…”
Section: Discussionmentioning
confidence: 99%